2008
DOI: 10.1021/ie071195n
|View full text |Cite
|
Sign up to set email alerts
|

Steam System Network Synthesis Using Process Integration

Abstract: SynopsisSteam boilers are used to generate steam in order to meet cold process heat requirements.The most common heat exchanger network layout associated with the boiler is a com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The steam flow rate to HENs can be reduced using pinch analysis. This has been done successfully by Coetzee and Majozi, 3 albeit without any consideration of the boiler efficiency. The problem addressed in this investigation can be formally stated as follows.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The steam flow rate to HENs can be reduced using pinch analysis. This has been done successfully by Coetzee and Majozi, 3 albeit without any consideration of the boiler efficiency. The problem addressed in this investigation can be formally stated as follows.…”
Section: Problem Statementmentioning
confidence: 99%
“…The following section elaborates on the graphical targeting technique developed by Coetzee and Majozi. 3 Their work focuses purely on streams that appear on the "hot" side of the process integration process. This is shown in Figure 1 below.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamic method is generally used to analyze the energy recovery or usage conditions of the steam system in an industry process. Optimization has then focused mainly to increase the energy utilization and exploit the benefit of maximizing process–process integration. Nishio et al proposed a design method for utility systems. This method is based on the estimation of thermodynamic losses and the irreversibility in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Gorsek et al presented modified site sink source profiles to determine energy saving potential by integration of existing plant with other plants. The graphical and mathematical techniques for targeting and network synthesis were presented by Coetzee and Majozi to reduce steam flow rate without compromising the duty requirements of the process heat exchangers. Matsuda et al demonstrated improvement in energy savings potential via integration of multiple plants using Total Site Analysis for a group of industries.…”
Section: Introductionmentioning
confidence: 99%